The Application of the Paddy Pawn System in an Islamic Perspective (Case Study of Trebungan Village Mlandingan Situbondo District) - Saifuddin Saif (Iqtishodiyah : Jurnal Ekonomi dan Bisnis Islam, 2021)
The pawning system practiced by the people of Des. Trebungan Kec. Mlandingan Kab. Situbondo is a customary system, which has lasted a long time and is still in effect today. This system arose because of the urgent need of those who mortgaged their fields, both because of the consumptive and productive needs. This research uses the qualitative method of applied research because it includes the researcher's effort to apply something new to the object of research. The results of the study found that the rice field pawn practiced by the community generally indicates the existence of a ribawi system and a form of denial, and is far from ta'awun. The Pawn Paddy solution in Islamic law is as follows: First, the Qardh al-hasan contract provides a loan with the condition that the fields are used as debt collateral to avoid fraud and fraud and there is no excess when returning the debt. Second, the al-mudharabah contract is intended for rice field owners to give profit sharing to murtahin until the capital used is paid off. And third, the al-bai al-murabahah murtahin contract will buy goods according to the wishes of Rahin and Rahin will provide benefits to the murtahin according to the agreement when it will last until the specified time limit.